INFORMATION SUPPORT OF UKRAINIAN STATE EUROPEAN INTEGRATION POLICY AND ITS ROLE IN REGULATING THE BUSINESS ENVIRONMENT - Revenko , O. V.; Revenko , T. V (Theory and Practice of Public Administration, 2021)
The main task for Ukraine in the European integration process is rapid and practical implementation of the announced reforms in various areas (economic, social, legal, financial etc.), bringing them to a logical conclusion, fulfilling the relevant commitments. Takin this into account, the situation with information support of the state European integration policy of Ukraine should be considered directly in close connection with the instruments of business environment regulation. In the article as a purpose of research the substantiation of directions development of information maintenance of Ukrainian state European integration policy taking into account its influence on process of business environment regulation is chosen. The place of information support of state European integration policy among other types of state policies is theoretically substantiated. It has been found to have a significant impact on the business environment development. And, therefore, the system of information support of state European integration policy in the field of business regulation has the specificity and scientific interest. Based on the analysis of the transitivity indicators dynamics of Ukraine, the peculiarities of the transition period and expedient directions of information policy implementation on the European vector of development are determined. The existing mechanism of information support of Ukrainian state European integration policy is investigated. It is proposed to consider the following levels of business development in the strategic context when assessing the information support system of state European integration policy: institutional, economic-regulatory, information-communicative and behavioral. The main components of the business environment that are extremely important in the analysis of the European integration process in Ukraine are identified. The main condition for the effectiveness of measures to improve the components of state regulation mechanism of business environment should be close coordination of these measures with socio-economic transformations in other areas, which will be accompanied by the establishment of certain information links. An important factor in success is the adherence to the principle of consistency and ease of information and analytical support components of European integration processes, as well as a positive perception of European values within the country.